A NIR spectral sequence of O-type supergiants - Giudici Michilini, Federico Nicolás (2021)
The study of spectral morphology is a powerful tool for understanding the fundamental properties of stars. The spectral classification scheme for O stars was revisited and a new set of spectral standard stars was proposed for all sub-types between 02 and BO and for all luminosity classes. We are working on the construction of a spectral atlas with high quality observations between 0.85 — 2.5 pm. Observations for this project have begun seven years ago, and they are carried out with the GNIRS (Gemini Observatory) and FIRE (Las Campanas Observatory) spectrographs. We present here a second batch of results, including the spectra of a complete temperature sequence of supergiant standard stars in the J, H and A'-bands. The analysis of this data set implies that it is possible to define spectral classification criteria using the He I and He π lines present in it.